Treatment of Femoral Vein Obstruction Concomitant with Iliofemoral Stenting in Patients with Severe Post-thrombotic Syndrome. (February 2018) - Ye, Kaichuang; Shi, Huihua; Yin, Minyi; Qin, Jinbao; Yang, Xinrui; Liu, Xiaobing; Jiang, Mier; Lu, Xinwu
Abstract : Background: The aim was to assess the clinical and anatomical outcomes of iliofemoral stenting, with concomitant femoral stenting or balloon angioplasty alone, in patients with severe post-thrombotic syndrome (PTS) and compromised inflow. Methods: A database of patients with severe PTS who successfully underwent endovascular iliofemoral stenting was reviewed retrospectively. Patients with impaired inflow with chronic post-thrombotic obstructive lesions in the femoral vein (FV), but patent profunda vein, were selected and divided into two groups: the FV stenting (FV-S) group and the FV angioplasty (FV-A) group. Patients in the FV-S group were treated with concomitant iliofemoral and FV stenting, and patients in the FV-A group were treated with iliofemoral stenting and balloon angioplasty alone of the obstructed femoral vein. The clinical and stent outcomes were recorded and compared in the two groups. Results: There were 45 patients in the FV-S group and 69 patients in the FV-A group. The groups were well matched for age, gender, and diseased limbs. The pre-procedural symptoms, CEAP classifications, VCSS scores, Villalta scores, and prevalence of active ulcers were also similar between the two groups. Immediate failure (<30 days post-procedure) in the femoral segment occurred more frequently in the FV-A group (70% in FV-A group vs. 24% in FV-S group, p  < .001); however, all treated femoral vein segments had occluded at 12 months. There was no significant difference between the FV-S and FV-A groups in cumulative primary and secondary patency rates of the iliofemoral stent at 3 years (55% vs. 52%, p  = .71, and 77% vs. 85%, p  = .32, respectively). Complete pain relief, swelling relief, VCSS score, Villalta score, and freedom from ulcers at a median of 22 months (1–48 months) following the procedure were similar in the two groups. Conclusions: Stent placement to treat post-thrombotic iliofemoral obstruction with concomitant obstructed femoral vein but patent profunda vein shows cumulative patency rates and clinical outcomes similar to previous reports. Adjunctive femoral stenting or angioplasty of the obstructed femoral vein does not appear to improve clinical or stent outcomes in patients with severe PTS.